Well-being inequality and reference groups: An agenda for new research - Bernard M. S. van Praag (Center for Economic Studies and ifo Institute (CESifo), 2010)
It is argued that the concept of well-being inequality cannot be properly defined without taking the referencing process into account. The reference effect depends on how frequently individuals compare with others and on the degree of social transparency in society. In this paper we employ the reference- extended model for incorporating the concept of happiness inequality in happiness studies. We plead for an extension of the present happiness paradigm by setting up a new additional agenda for empirical research in order to get quantified knowledge about the referencing process.
Keywords: D31; D62; D63; I31; 330; subjective well being; happiness; inequality; reference group; Lebenszufriedenheit; Soziale Ungleichheit; Interpersoneller Nutzenvergleich